Necrotizing gastritis and perforation in an extremely low birthweight infant - Patrick T. Reeves; James A. Lee; Andrew J. Delle Donne; Christian L. Carlson; Maribel M. Morgan; Jonathan B. Shapiro (Elsevier, 2017)
Pneumatosis intestinalis (PI) is a well-documented phenomenon characterized by the presence of gas within the wall of the intestine and is often a sign of necrotizing enterocolitis (NEC). NEC and PI are both abundantly described in the literature, and are associated with significant morbidity and mortality, particularly for extremely low birth weight (ELBW) infants. Although less common, gastric pneumatosis and necrotizing gastritis have been reported in association with a variety of etiologies, but generally occur concurrently with fulminant NEC. To date, there are no cases detailing survival or management of necrotizing gastritis with gastric perforation in ELBW infants. We present a unique case of necrotizing gastritis in an ELBW infant of 23 2/7 weeks gestation, without any evidence of NEC or other identifiable etiologies, who developed a gastric perforation related to the disease and subsequent management of that infant from diagnosis through discharge.